PENGARUH METODE PROBLEM-BASED LEARNING DAN DIRECT TEACHING TERHADAP HASIL BELAJAR ALAT UKUR - Heru Raharjo (Jurnal Taman Vokasi, 2015)
This study aims to investigate: (1) the difference of learning outcomes between students taught using PBL and direct teaching method, high and low motivation, high and low creativity; (2) the effect of interaction between learning method, motivation and creativity on learning outcomes; (3) the difference of learning outcomes between students taught using PBL and direct teaching method in terms of motivation and creativity. This is quasy-experimental research with a factorial design. Data were analysed statiscally using Anava and t-test. The result shows that: (1) there was difference of learning outcomes between students taught using PBL and direct teaching method; (2) there was no difference of learning outcomes between students who have high and low motivation; (3) there was difference of learning outcomes between students who have high and low creativity; (4) there was interaction effect between learning method and motivation on learning outcomes; (5) there was interaction effect between learning method and creativity on learning outcomes; (6) there was difference of learning outcomes between students taught using PBL and direct teaching method in term of motivation; (7) there was difference of learning outcomes between students taught using PBL and direct teaching method in term of creativity.